1995
DOI: 10.1002/ajh.2830480402
|View full text |Cite
|
Sign up to set email alerts
|

Idiopathic osteonecrosis, hypofibrinolysis, high plasminogen activator inhibitor, high lipoprotein(a), and therapy with stanozolol

Abstract: In five patients with idiopathic osteonecrosis (ON) of the hip, four having hypofibrinolysis mediated by high plasminogen activator inhibitor (PAI-Fx), and one with high Lp(a), our specific aim was to determine whether therapy (Rx) with the anabolic-androgenic steroid, Stanozolol (6 mg/day), would normalize PAI-Fx and Lp(a) and thus potentially ameliorate ON. Prior to Rx, none of the four patients with high PAI-Fx could normally elevate tissue plasminogen activator (tPA-Fx) after 10 min venous occlusion at 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 32 publications
3
47
0
Order By: Relevance
“…In a pilot study, we have given stanozolol (6 mg/day) to three of our nine patients with primary high PAI, inability to initiate fibrinolysis, and idiopathic osteonecrosis. In two patients, after 12 weeks of therapy, PAI-Ag and PAI-Fx were normalized, and stimulated tPA-Fx became normal [40]. Unexpectedly, but encouragingly, after 12 weeks of treatment, one of these two patients, who had been able to walk painfully for only one block prior to treatment, walked 2 miles every day despite radiographic progression of osteonecrosis [40].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In a pilot study, we have given stanozolol (6 mg/day) to three of our nine patients with primary high PAI, inability to initiate fibrinolysis, and idiopathic osteonecrosis. In two patients, after 12 weeks of therapy, PAI-Ag and PAI-Fx were normalized, and stimulated tPA-Fx became normal [40]. Unexpectedly, but encouragingly, after 12 weeks of treatment, one of these two patients, who had been able to walk painfully for only one block prior to treatment, walked 2 miles every day despite radiographic progression of osteonecrosis [40].…”
Section: Discussionmentioning
confidence: 93%
“…Since PA1 can be reduced and fibrinolytic activity increased by the anabolic steroid stanozolol [38,39], we speculate that, when primary osteonecrosis is diagnosed early, prior to segmental collapse of the femoral head, it may be possible to treat defective fibrinolysis and, hence, to arrest progression or induce regression of osteonecrosis of the hip [40]. In a pilot study, we have given stanozolol (6 mg/day) to three of our nine patients with primary high PAI, inability to initiate fibrinolysis, and idiopathic osteonecrosis.…”
Section: Discussionmentioning
confidence: 99%
“…With regard to pharmacological treatment, Boos [7] reported good clinical results with sympathetic nerve blockade with bupivacaine in three patients, but no improvement in pathological MRI signal patterns. Laroche [32] reported some pain reduction in a small controlled study with nifedipine, and Glueck [33] presented preliminary data using stanozolol in the treatment of avascular necrosis, but these studies were performed in patients with avascular necrosis only and were not followed up in the literature. Lakhanpal [34] found no beneficial effect with the use of calcitonin, antituberculosis drugs, prednisone and lumbar sympathectomy with bupivacaine.…”
Section: Discussionmentioning
confidence: 98%
“…In addition to etiological factors, NICO has worsening and hereditary factors associated to the disease. Researchers 13,15,16 have concluded that patients with such neuralgia have differences in coagulation factors which are common as hereditary forms of thrombophilia and hypofibrinolisis, also related to risk factos such as femoral head osteonecrosis. Seventy-one percent of NICO cases are caused by alcohol abuse, trauma, prednisone, estrogen, pregnancy, sickle cell anemia, lupus erythematosus and use of chemotherapy for malignant neoplasias.…”
Section: Development Mechanism and Etiologymentioning
confidence: 99%
“…Current studies describe ischemic alveolar bone marrow coagulation disorders as the cause for NICO, which may also be the result of thrombosis with or without hypofibrinolysis, which would obstruct vascular spaces impairing blood flow in the region [12][13][14] . So, it could be treated with anticoagulants or anabolic steroids [15][16][17][18] . Other therapeutic options would be regional osteotomy and curettage of the painful area, or osteotomy associated to local application of absorbable gelatine sponge associated to tetracycline, with tetracycline and cephalexin, or clindamicine with gentamicine [1][2][3][4]9 .…”
Section: Introductionmentioning
confidence: 99%